2006
DOI: 10.1158/1078-0432.ccr-06-1101
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Loss of Expression of Argininosuccinate Synthetase in Malignant Pleural Mesothelioma Is a Biomarker for Susceptibility to Arginine Depletion

Abstract: Purpose: Malignant pleural mesothelioma (MPM) is an increasing health burden on many societies worldwide and, being generally resistant to conventional treatment, has a poor prognosis with a median survival of <1year. Novel therapies based on the biology of this tumor seek to activate a proapoptotic cellular pathway. In this study, we investigated the expression and biological significance of argininosuccinate synthetase (AS), a rate-limiting enzyme in arginine production. Experimental Design: Initially, we do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
161
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 163 publications
(167 citation statements)
references
References 27 publications
5
161
0
1
Order By: Relevance
“…Preclinical models demonstrated that arginine deprivation is synthetically lethal in MPM cells that do not express argininosuccinate synthetase 1 (ASS1) (161). Approximately 60% of MPM tumors have loss of ASS1.…”
Section: Arginine Depletionmentioning
confidence: 99%
“…Preclinical models demonstrated that arginine deprivation is synthetically lethal in MPM cells that do not express argininosuccinate synthetase 1 (ASS1) (161). Approximately 60% of MPM tumors have loss of ASS1.…”
Section: Arginine Depletionmentioning
confidence: 99%
“…Nevertheless, Dillion et al have reported that all 51 hepatoma tumor samples are deficient in ASS by immunohistochemical staining [36] Antitumor Activity of ADI-PEG20 in other Cell Lines Certain mesothelioma cell lines (2591 and MSTO) do not express ASS and are sensitive to ADI-PEG20 while two other cell lines (226,2461) express high levels [17]. Immunohistochemical study showed 63% of mesothelioma express low levels of ASS [17]. Based on this study, clinical trials in mesothelioma have been initiated [Szlosarck, personal communication].…”
Section: Antitumor Activity Of Adi-peg20 In Hepatocellular Carcinomamentioning
confidence: 99%
“…In fact, our preliminary data showed increased Beclin1 in these cell lines with Mel1220 having the highest Beclin1 levels. In mesothelioma, Szlosarek has shown that arginine depletion induces BAX conformation changes and mitochondrial inner membrane depolarization in ASS(−) cells which leads to apoptosis [17,39]. Thus, the mechanism(s) which lead to apoptosis is complex and may be different among all the cell lines which lack ASS expression.…”
Section: Adi-peg20 Induces Apoptosis In Melanoma Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations